PEUSIJUEK RITUAL: EMBEDDED CUSTOMS AND THE FORMATION OF SOCIAL IDENTITY IN ACEH - Rizqi Muhammad Rayyan; Agam Muhammad Rizki (Jurnal Analisa Sosiologi, 2025)
The peusijuek ritual is a deeply embedded custom in the lives of the Acehnese people, serving as a symbol that shapes social and cultural identity. This study aims to analyze the historical aspects of peusijuek and its role in forming social identity in Aceh. Through a qualitative approach, data were collected via in-depth interviews with community leaders and literature studies. The results show that peusijuek is not merely a ceremonial ritual but a bridge connecting individuals with the community, creating solidarity, and strengthening the harmony between local traditions and Islamic religious values. The ritual involves symbolic elements such as rice and leaves, representing prosperity and peace. As a practical implication, this study recommends integrating peusijuek values into a local wisdom-based education curriculum to maintain the cultural identity of the younger generation amidst modernization.